2021
DOI: 10.1093/ecco-jcc/jjab116
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient, Fibre, and FODMAP Intakes and Food-related Quality of Life in Patients with Inflammatory Bowel Disease, and Their Relationship with Gastrointestinal Symptoms of Differing Aetiologies

Abstract: Background and Aims Certain foods are reported as gut symptom triggers in IBD, and fructans are shown to worsen non-inflammatory symptoms in inactive IBD, which may result in self-imposed dietary restrictions. The aim of this case-control study was therefore to investigate nutrient and FODMAP intakes, and the relationship between gut symptoms and dietary intake, in IBD. Methods Nutrient, fibre and FODMAP intakes were estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 61 publications
3
43
0
Order By: Relevance
“…For example, polyglycans have been observed to exacerbate inflammatory symptoms in inactive IBD patients without abdominal pain, diarrhea. 133 , 134 Dietary fiber is metabolized in the gut to SCFAs, resulting in the subsequent activation of GPCR and Treg, and resulting in a reduced inflammatory response and increased mucosal tolerance, thereby protecting CD patients. 135 , 136 In addition, the interaction between gut microbiota and dietary fiber and protein concentration alleviates inflammation and is also a factor that improves intestinal permeability in mice.…”
Section: Regulation Of the Intestinal Microbiota To Treat Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, polyglycans have been observed to exacerbate inflammatory symptoms in inactive IBD patients without abdominal pain, diarrhea. 133 , 134 Dietary fiber is metabolized in the gut to SCFAs, resulting in the subsequent activation of GPCR and Treg, and resulting in a reduced inflammatory response and increased mucosal tolerance, thereby protecting CD patients. 135 , 136 In addition, the interaction between gut microbiota and dietary fiber and protein concentration alleviates inflammation and is also a factor that improves intestinal permeability in mice.…”
Section: Regulation Of the Intestinal Microbiota To Treat Ibdmentioning
confidence: 99%
“…Whether diet intervention can affect the structure and abundance of host intestinal microbiota species is unknown, but studies have shown that symptoms in IBD patients are triggered by some specific dietary conditions. For example, polyglycans have been observed to exacerbate inflammatory symptoms in inactive IBD patients without abdominal pain, diarrhea 133,134 . Dietary fiber is metabolized in the gut to SCFAs, resulting in the subsequent activation of GPCR and Treg, and resulting in a reduced inflammatory response and increased mucosal tolerance, thereby protecting CD patients 135,136 .…”
Section: Regulation Of the Intestinal Microbiota To Treat Ibdmentioning
confidence: 99%
“…The instrument, the FR-QoL-29, is written in English and consists of 29 items that people with IBD rate using a Likert scale. It has been used to show impairments in FR-QoL, and their associated factors, in patients with IBD in a range of English-speaking countries, including the United Kingdom [ 17 , 18 ], United States [ 12 ], Australia [ 19 ] and New Zealand [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…One uncontrolled trial in 25 people and one RCT in 70 people in coeliac disease with persisting symptoms and histologically normal villi-reported gastrointestinal symptom improvement in response to a low FODMAP diet [35,36 ▪ ]. In IBD, intakes of total FODMAPs, fructans and sorbitol are lower in people with active disease, even when adjusted for total energy intake [37 ▪ ]. Evidence from a sham-controlled RCT in 52 people with quiescent IBD who were experiencing ongoing gastrointestinal symptoms reported the low FODMAP diet was superior to sham diet for global symptoms and health-related quality of life, although not for individual symptoms such as pain and bloating [38].…”
Section: Low Fodmap Diet In Other Gastrointestinal Disordersmentioning
confidence: 99%